2004
DOI: 10.1111/j.0019-2805.2004.01817.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinases and their inhibitors during the resorption of schistosome egg‐induced fibrosis in praziquantel‐treated mice

Abstract: SUMMARYSchistosomiasis mansoni is a tropical helminthic disease characterized by parasite egginduced granulomatous in¯ammation and cumulative ®brosis. Because ®brosis is in¯uenced by the imbalance between degradative matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs), we analysed the resorption of ®brous tissue and MMP/TIMP expression in the livers of S. mansoni-infected and praziquantel-cured mice. Worm elimination signi®cantly enhanced survival rate, ameliorated the granulom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 45 publications
4
48
0
Order By: Relevance
“…They speculated that alternate pathways, mediated by a 1-macroglobulin or plasminogen activator inhibitor 1, could have compensated for the loss of inhibition by TIMP. Singh et al (2004) recently found that praziquantel cure of infected mice strongly diminished TIMP-1 gene expression and promoted absorption of liver fibrosis. Moreover, intrahepatic injections of TIMP-1 antisense oligodeoxynucleotide suppress the expression of the TIMP-1 gene and lower the total collagen content of the livers of infected mice (unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…They speculated that alternate pathways, mediated by a 1-macroglobulin or plasminogen activator inhibitor 1, could have compensated for the loss of inhibition by TIMP. Singh et al (2004) recently found that praziquantel cure of infected mice strongly diminished TIMP-1 gene expression and promoted absorption of liver fibrosis. Moreover, intrahepatic injections of TIMP-1 antisense oligodeoxynucleotide suppress the expression of the TIMP-1 gene and lower the total collagen content of the livers of infected mice (unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxyproline assay was carried out based on the previously reported methodology (Bergman and Loxley 1963) using base rather than acid hydrolysis for the dissolution of tissue (Singh et al 2004). Briefly, liver tissue was weighed and incubated overnight at 37°C in 5% KOH (6 ml/100 mg tissue weight).…”
Section: Measurement Of Biochemical Parametersmentioning
confidence: 99%
“…Furthermore, there is evidence that treatment with praziquantel induces a change in the immune response that provides partial protection against schistosome infection, thus providing benefits that may extend beyond a transient reduction in levels of infection (21,40,42). Additionally, although the cumulative fibrosis that occurs during infection is mostly irreversible, periportal fibrosis regresses following eradication of the infection by chemotherapy (16,44,48).…”
mentioning
confidence: 99%